San Luis Obispo Creek Bridge - John H. Klopp::::::photographer::: (1949)
Below bridge 49-13, Old 101 Highway looking Northerly. Note sign upper left corner. Estimated water flow 5-6 cu. ft. per second. Dec. 12, 1949. Downstream from Joaquin L. Perreira. Upstream from Chas. F. Johnson.' Sign in upper left corner reads: 'Visit Reno's Palace Club Oldest in Nevada'